Platelet Rich Plasma (PRP) as an Enhancer of Wound Healing in Problematic Wounds: Our University of Port Harcourt Teaching Hospital (UPTH) Experience - Gbeneol, T. J.; Onwuagha, I. J. (British Journal of Healthcare and Medical Research, 2025)
Introduction: Problematic wounds are difficult to heal wound, as the timely and orderly manner of acute wound healing is disrupted and have defied the normal wound healing protocols, Platelet Rich Plasma PRP in the enhancement of tissue repair and cellular regeneration. Objective: To evaluate the effect of topical PRP in wound healing about time to heal, level of pain, and number of dressing changes. Methods: This is a prospective, randomized clinical study conducted at the outpatient clinic with 21 well-matched patients fulfilling the inclusion criteria. A 10 ml sample of fresh blood was drawn and centrifuged at 1800rpm for 10 minutes then 3500 rpm for 15 minutes to isolate the PRP. All patients with chronic ulcers were treated to receive dressings impregnated with PRP. Patients were followed up for 8 weeks to evaluate the wound characteristics, healing process, quality of granulation tissue, presence of exudate or slough, need for frequent changes of dressings, and associated pain levels. Data Analysis: collected were entered in Microsoft Excel 2010. Analysis was done using Epi-info version 7.0. Result: All patients with chronic ulcers received dressings infused with PRP. Assessments were conducted over an 8-week monitoring wound characteristics, healing progression, granulation tissue quality, presence of exudate or slough, necessity for frequent dressing changes, and associated pain levels. Conclusion: The results of this study depicted that Platelet Rich Plasma (PRP) is highly effective in the treatment of Problematic Wounds of various etiologies. PRP reactivates the healing and regeneration in problematic wounds.